Enhancement of Folliculogenesis by Fresh Onion Juice in a Rat Model - Yılmaz, Nafiye; Yorgancı, Ayçağ; İnal, Hasan A. and Seven, Banu and Timur, Hakan and Kalem, Müberra Namlı and Kalem, Ziya and Han, Özge and Bilezikçi, Banu (Current Traditional Medicine, 2021)
Aim: To evaluate the effects of fresh onion juice on female infertility. Background: Onion contains several antioxidants and has been used for the subfertile woman to achieve pregnancy by herbalists. Objective: This study was carried out to investigate the effects of fresh onion juice on ovarian folliculogenesis and implantation in rats. Methods: Female albino rats were divided into two groups: 5-day (one estrus cycle) and 10-day treatment (two estrus cycles) groups. The animals in the two groups were then divided into subgroups of the control group, 1 cc onion juice and 2 cc onion juice, each containing seven rats. At the end of the 5th and 10th days, ovarian volume and weight were measured, and the primordial, antral, and atretic follicles, and corpus lutea were counted. Vascular endothelial growth factor (VEGF) and endothelial nitric oxide synthase (eNOS) were evaluated both in the ovaries and in the endometrium immunohistochemically. Results: In the 5-day treatment group, ovarian weight and the antral follicle count were significantly higher in the 2 cc onion juice subgroup than the control group (p<0.05). In the 10-day treatment group, the antral follicle count was significantly higher both in 1cc and 2cc onion juice subgroups than the control group (p<0.05). There was also increased ovarian stromal VEGF in the 10-day 1cc onion juice subgroup (p<0.05). Conclusion: The results of our study showed that fresh onion juice could increase the number of antral follicles, which is an indicator of enhanced folliculogenesis.
Keywords: onion